Estimation of Radiation Dose Calculation on Non Static Organs - Novan Habiburrahman; Johan A.E. Noor; Unggul P. Juswono (Natural B, Journal of Health and Environmental Sciences, 2013)
In this study developed a program calculating the estimated radiation dose to the cancer by using a program that can run on a variety of computer operating systems platforms. The program used is a Java application programming interface (API) Greenfoot. The program determines the value of the accumulated dose received by each pixel in multiple beam irradiation with attenuation values obtained from the analysis of data Hounsfield value CT-scan. Hounsfield value of each pixel is generated based on the relationship value of grayscale linearity then. Hounsfield value of the CT-scan converted into the value of the gamma-ray attenuation. The dose received by the skin surface used as a reference to determine the length of time considered organ irradiation in static conditions on the program. Movement of the target irradiation in treatment may reduce the efficiency level of success. Moving organ radiation Treatment can be done. Radiation pulse period set for the radiation beam on the target in this phase organ reaches ± 60% of the maximum volume. A pulse rays will be effect the long exposure time can be calculated with the program.